1999
DOI: 10.1097/00001648-199907000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Asbestos and Smoking on Lung

Abstract: Few studies have investigated the association between body mass index and fecundability, that is, the ability to conceive in a menstrual cycle, among fertile women with normal menstrual cycle pattern. We examined the independent and combined effects of duration and regularity of the menstrual cycle, body mass index, and fecundability from records on pregnant women attending antenatal care at Odense University Hospital, Denmark, between 1972 and 1987. We included only the first birth of each woman who had plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(67 citation statements)
references
References 34 publications
3
59
1
4
Order By: Relevance
“…Therefore, the results cannot be extrapolated directly to the general population, but this occupational group is of special interest for two reasons: 1) this group of people may be at an increased risk of smoking-induced diseases, since persons exposed to asbestos are more likely to be susceptible to the adverse effects of smoking, as has been shown in the case of lung cancer [6]; and 2) workers exposed to asbestos (especially those with pleural plaques) are screened radiologically in many countries [7][8][9] and smoking-related CT findings may thus be a major differential diagnostic problem.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results cannot be extrapolated directly to the general population, but this occupational group is of special interest for two reasons: 1) this group of people may be at an increased risk of smoking-induced diseases, since persons exposed to asbestos are more likely to be susceptible to the adverse effects of smoking, as has been shown in the case of lung cancer [6]; and 2) workers exposed to asbestos (especially those with pleural plaques) are screened radiologically in many countries [7][8][9] and smoking-related CT findings may thus be a major differential diagnostic problem.…”
Section: Discussionmentioning
confidence: 99%
“…The synergy index [S ¼ ERR 11 =ðERR 10 þ ERR 01 Þ] was defined as the ratio of the observed joint excess relative risk of both silicosis and smoking to the sum of the separate estimates (excess relative risk). 37 ERR was the excess relative risk for effects associated with smoking and silicosis on the risk of lung cancer individually (ERR 01 or ERR 10 ) or in combination (ERR 11 ) by subtracting unity from the relevant relative risks. 37 If S equaled one, the joint effect between smoking and silicosis on lung cancer would conform to an additive model.…”
Section: The Assessment Of Multiplicative and Additive Interactionsmentioning
confidence: 99%
“…37 ERR was the excess relative risk for effects associated with smoking and silicosis on the risk of lung cancer individually (ERR 01 or ERR 10 ) or in combination (ERR 11 ) by subtracting unity from the relevant relative risks. 37 If S equaled one, the joint effect between smoking and silicosis on lung cancer would conform to an additive model. In case the joint effect departed from an additive model, then S should not be equal to one.…”
Section: The Assessment Of Multiplicative and Additive Interactionsmentioning
confidence: 99%
“…In fact, smoking was found to be the main risk factor but its interaction with asbestos was not totally clear (3). Some studies showed a multiplicative effect, whereas other studies suggested an additive model (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%